2018
DOI: 10.1016/j.devcel.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The HCMV Assembly Compartment Is a Dynamic Golgi-Derived MTOC that Controls Nuclear Rotation and Virus Spread

Abstract: Human cytomegalovirus (HCMV), a leading cause of congenital birth defects, forms an unusual cytoplasmic virion maturation site termed the "assembly compartment" (AC). Here, we show that the AC also acts as a microtubule-organizing center (MTOC) wherein centrosome activity is suppressed and Golgi-based microtubule (MT) nucleation is enhanced. This involved viral manipulation of discrete functions of MT plus-end-binding (EB) proteins. In particular, EB3, but not EB1 or EB2, was recruited to the AC and was requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 67 publications
2
77
0
Order By: Relevance
“…After washing, detection was performed using Pierce ECL western blot substrate (Thermo Fisher) followed by exposure to X-ray film. Western blots were quantified using densitometry as described previously (Procter et al, 2018).…”
Section: Western Blottingmentioning
confidence: 99%
“…After washing, detection was performed using Pierce ECL western blot substrate (Thermo Fisher) followed by exposure to X-ray film. Western blots were quantified using densitometry as described previously (Procter et al, 2018).…”
Section: Western Blottingmentioning
confidence: 99%
“…As a highly dynamic organelle, Golgi serves as a membrane scaffold for multiple viruses, including infectious hepatitis C virus, enteroviruses, poliovirus, foot-and-mouth-disease virus, dengue virus, coronavirus, Kunjin virus, tick-borne encephalitis virus, rubella virus, and bunyamwera virus (Miller and Krijnse-Locker 2008;Harak and Lohmann 2015;Risco et al 2003;Salanueva et al 2003;Delgui et al 2013;Westerbeck and Machamer 2015), and is frequently fragmented after infection (Campadelli et al 1993;Salanueva et al 2003;Yadav et al 2016;Avitabile et al 1995;Lavi et al 1996;Hansen et al 2017;Rebmann et al 2016). Viruses use Golgi membranes directly and/or hijack master controllers of Golgi biogenesis and trafficking to generate vesicles that are used as the site of viral RNA replication (Quiner and Jackson 2010;Hansen et al 2017;Short et al 2013), wrapping (Sivan et al 2016;Alzhanova and Hruby 2007;Alzhanova and Hruby 2006;Nanbo et al 2018;Lundu et al 2018;Procter et al 2018), intracellular transduction (Nonnenmacher et al 2015), and secretion ). Viral infection triggers Golgi fragmentation via diverse mechanisms, ranging from phosphorylating key Golgi structural proteins such as GRASP65 (Rebmann et al 2016), activating the Src kinase to phosphorylate the Dynamin 2 GTPase (Martin et al 2017), targeting the immunity-related GTPase M (IRGM) to the Golgi to induce GBF1 phosphorylation (Hansen et al 2017), modulating vesicular trafficking (Yadav et al 2016;Johns et al 2014), to impeding the major histocompatibility complex (MHC) class I trafficking, antigen presentation, and/or cytokine secretion Rohde et al 2012).…”
Section: Viral Infectionmentioning
confidence: 99%
“…Virologists often think of microtubules in terms of viral entry, and cell biologists largely think about their formation in terms of centrosomes. The work presented here by Procter et al (2018) will help each group to reconsider their long-held impressions of microtubule function and regulation. Furthermore, the authors demonstrate how live-cell imaging of viral infections is particularly amenable to the study of rare or complex cellular events.…”
mentioning
confidence: 99%
“…Over the hours, decades, and millennia, HCMV has learned a lot of cell biology during these infections. In this issue of Developmental Cell, Procter et al (2018) report some of that knowledge that they have pried loose by using live-cell imaging to watch, in real time, how HCMV alters cellular architecture to facilitate its own assembly. The authors observed nuclear somersaults and Golgi-derived structures splitting and fusing.…”
mentioning
confidence: 99%
See 1 more Smart Citation